THE INFLUENCE OF PRODUCT QUALITY PRICE AND PROMOTION ON PURCHASE DECISIONS OF HIJAB RABBANI SYAR'I MODEL AT THE RABBANI VILLA MUTIARA CIKARANG SELATAN STORE - Yuniwinarti Yuniwinarti; Etty Zuliawati Zed (SEAN Institute, 2023)
The development of fashion in Indonesia is currently growing rapidly. Public interest in the hijab, which is part of Muslim fashion, is increasing day by day. Rabbani is one of the first and largest fashion brand product companies in Indonesia by releasing flagship products in the form of instant headscarves and other products. Many factors are done by consumers before deciding to buy a product. Purchasing decisions by consumers are decisions that involve perceptions of product quality, price and promotion. The formulation of the problem in this study is to find out whether product quality, price and promotion can influence purchasing decisions. As well as the objectives of each variable Product Quality, Price and Promotion can influence Purchase Decisions on Hijab Rabbani Syar'i Models at the Rabbani Villa Mutiara Store, Cikarang Selatan. This study uses quantitative methods in data collection and data analysis. The population used in this research is Rabbani hijab users at the Rabbani Villa Mutiara Cikarang Store with a sample size of 120 people. The data analysis techniques used are validity and reliability tests, classic assumption tests, and multiple regression analysis using SPSS Ver. 29. Based on the analysis of this research, the results show that 1) product quality has a positive and significant effect on purchasing decisions for the Rabbani hijab syar'i model at the Rabbani Villa Mutiara Cikarang store, 2) price has a positive and significant effect on purchasing decisions for the Rabbani hijab syar'i model at the Rabbani Villa Mutiara Cikarang store, 3) promotion has a positive and significant effect on purchasing decisions for the Rabbani hijab syar'i model at the Rabbani Villa Mutiara Cikarang store, 4) product quality, price and promotion have a positive and significant effect on purchasing decisions for the Rabbani hijab syar'i model at the Rabbani Villa Mutiara Cikarang store.